2021
DOI: 10.1093/cid/ciab289
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens That Cause Acute Febrile Illness Among Children and Adolescents in Burkina Faso, Madagascar, and Sudan

Abstract: Background The etiology and optimal clinical management of acute febrile illness (AFI) is poorly understood. Methods Blood samples taken from study participants with acute fever (≥37.5°C) or a history of fever and recruited into the previous Typhoid-Fever-Surveillance-in-Africa (TSAP) study were evaluated using a polymerase chain reaction (PCR)-based TaqMan-Array Card designed to detect a panel of bacterial, viral and parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…In our meta-analysis (Figure 5), cross-sectional studies in Cameroon [30, 45], and Kenya [22] revealed significantly lower odds of co-infection in contrast with the absence of acute dengue infections (OR: 0.60; 95% CI, 0.42 – 0.87). Cross-sectional studies in Nigeria [16, 18, 20, 25, 32, 33, 35], Tanzania [17], Sierra Leone [23], Democratic Republic of Congo (DRC) [34], Cameroon [31], Sudan [40, 42], and Senegal [21] indicated no significant odds of co-infection in comparison with acute dengue negatives (OR = 1.07; 95% CI = 0.58, 1.94). Studies in Ethiopia [44], Nigeria [29], Tanzania [36], Cameroon [43], and Kenya [39], on the other hand, indicated significantly higher odds of concurrent infection to acute dengue negatives (OR = 4.56; 95% CI = 3.29, 6.33).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our meta-analysis (Figure 5), cross-sectional studies in Cameroon [30, 45], and Kenya [22] revealed significantly lower odds of co-infection in contrast with the absence of acute dengue infections (OR: 0.60; 95% CI, 0.42 – 0.87). Cross-sectional studies in Nigeria [16, 18, 20, 25, 32, 33, 35], Tanzania [17], Sierra Leone [23], Democratic Republic of Congo (DRC) [34], Cameroon [31], Sudan [40, 42], and Senegal [21] indicated no significant odds of co-infection in comparison with acute dengue negatives (OR = 1.07; 95% CI = 0.58, 1.94). Studies in Ethiopia [44], Nigeria [29], Tanzania [36], Cameroon [43], and Kenya [39], on the other hand, indicated significantly higher odds of concurrent infection to acute dengue negatives (OR = 4.56; 95% CI = 3.29, 6.33).…”
Section: Resultsmentioning
confidence: 99%
“…Sudan [40,42], and Senegal [21] indicated no significant odds of co-infection in comparison with acute dengue negatives (OR = 1.07; 95% CI = 0.58, 1.94). Studies in Ethiopia [44], Nigeria [29],…”
Section: The Interaction Of Plasmodium and Dengue Virusesmentioning
confidence: 87%
See 2 more Smart Citations
“…As a result, many of these AFI patients are treated according to clinical presentation [8]. The reliance on clinical presentation alone can lead to the misuse of antimicrobials [9] as well as poor patient outcomes. This is particularly the case for Zika virus, which like many other causes of AFI, is difficult to diagnose [10] and may clinically mimic other infections such as Salmonella enterica, Listeria spp., and Brucella spp.…”
Section: Introductionmentioning
confidence: 99%